Calsyntenin-3 suppresses inflammation via inhibition of TLR N-glycosylation and membrane localization - Jiaqi Duan; Shikun Zhang; Bingjing Wang; Yin Liu; Lun Liu; Yang Liu; Jiacheng Wu; Xuetao Cao (Proceedings of the National Academy of Sciences, 2026)
Excessive innate immune activation drives uncontrolled inflammation and multiple inflammatory diseases. Proper N-glycosylation of membrane-associated Toll-like receptor 4 (TLR4) is essential for its trafficking to the cell membrane and subsequent innate activation, yet the mechanisms regulating this process remain poorly understood. Through a genome-wide CRISPR screening, we identify calsyntenin-3 (CLSTN3) as a potent suppressor of TLR4-triggered inflammation in macrophages. Mechanistically, CLSTN3 binds to the oligosaccharyltransferase (OST) subunit DDOST, inhibiting its interaction with the catalytic subunit STT3A and impairing OST complex assembly, which reduces N-glycosylation and membrane translocation of TLR4. Furthermore, CLSTN3 also suppresses membrane translocation and activation of other TLRs, including TLR3, TLR7 and TLR9. In addition, CLSTN3 expression is reduced in multiple inflammatory diseases and correlates negatively with the cytokine expression in sepsis. Our findings reveal CLSTN3 as a potent suppressor of inflammation by controlling membrane-associated TLR translocation via glycosylation inhibition, presenting a target for intervening inflammatory diseases.